PENGARUH PERPUTARAN MODAL KERJA TERHADAP PROFITABILITAS PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Dewi, Lisnawati; Rahayu, Yuliastuti (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to examine the influence of cash turnover, account receivable turnover, andinventory turnover to the profitability in the manufacturing companies in consumption goods industry sectorwhich are listed in Indonesia Stock Exchange (IDX) in 2010-2014 periods. The samples are 19 companies whichhave been selected by using purposive sampling. The financial statement data has been obtained from theIndonesia Stock Exchange (IDX). The research method has been done by using quantitative method and multiplelinier regressions with the aplication instrument of SPSS (Statistical Product and Service Solutions). The resultof this research shows that cash turnover and inventory turnover do not have any influence to the profitabilitywhereas the account receivable turnover has an influence to the profitability. The value of adjusted R square is0.113 which shows that all of independent variables which are cash turnover, account receivable turnover andinventory turnover can explain the dependent variable i.e. profitability is 11.3% and the remaining is 88.7%which is influenced by other factors which are not included in this model.Keyword: Profitability, Cash Turnover, Receivable Turnover, Inventory Turnover.